SIMULATION AND PSYCHOLOGICAL TRAININGS AS METHODS OF PREVENTING EMOTIONAL BURNOUT IN DOCTORS - Lefterov, V.O.; Timchenko, О.V.; Tsilmak, О.M.; Ignatieva, I.I. (World of Medicine and Biology, 2020)
The article analyzed the problem of emotional burnout in doctors, as well as the features of using and implementing medical simulation tools in the training process of medical specialists. The results of an empirical study of the simulation and psychological training effects on the psychological correction and the burnout syndrome prevention in doctors were presented. It was found that after these trainings doctors have reduced rates of emotional exhaustion, depersonalization, and improved well-being and mood. It was recommended to perform diverse psychological trainings and other psychological support and consulting procedures in the simulation training system.
Keywords: medical simulation tools; simulation training; psychological training; burnout syndrome; psychological correction and prevention